Implementation of the Discussion Method to Increase the Learning Enthusiasm of Grade IX Students in the Subject of Islamic Cultural History (Case Study at MTs Nurul Iman Rajeg-Tangerang Regency) - Nasrullah, Nasrullah; Zakiah, Ayu Rohmatu (Universitas Pakuan, 2025)
Teachers as class supervisors are required to have insight and creativity in their respective fields, so a teacher must be able to create interactions in the teaching and learning process. Creating interactions in the classroom is influenced by the existence of a method in learning. This shows how important a method is in the teaching and learning process. Of the many methods available, one of them is the discussion method, a method that emphasizes active interaction between students and teachers or between students themselves. To solve problems, exchange ideas, and achieve shared understanding. Seeing this, the author is interested in raising this problem into a study. The goal is to determine the application of the discussion method in increasing the enthusiasm for learning of grade IX students in the subject of Islamic cultural history, a case study at MTS Nurul Iman. This study departs from the results of observations, if the application of the discussion method in learning Islamic cultural history is applied more frequently to students, then the enthusiasm for learning in students can increase. With the application of the discussion method in learning.